2014
DOI: 10.1111/ele.12305
|View full text |Cite
|
Sign up to set email alerts
|

Trophic disruption: a meta‐analysis of how habitat fragmentation affects resource consumption in terrestrial arthropod systems

Abstract: Habitat fragmentation is a complex process that affects ecological systems in diverse ways, altering everything from population persistence to ecosystem function. Despite widespread recognition that habitat fragmentation can influence food web interactions, consensus on the factors underlying variation in the impacts of fragmentation across systems remains elusive. In this study, we conduct a systematic review and meta-analysis to quantify the effects of habitat fragmentation and spatial habitat structure on r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
103
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 86 publications
(121 reference statements)
7
103
2
Order By: Relevance
“…The main exceptions are studies dealing with food webs and other interactions between different trophic levels (e.g., Galetti et al 2013, Martinson andFagan 2014). Our results suggest that interactions among species within the same trophic level can play an important, yet overlooked, role in regulating the effects of fragmentation on biodiversity and ecosystem function.…”
Section: Discussioncontrasting
confidence: 66%
“…The main exceptions are studies dealing with food webs and other interactions between different trophic levels (e.g., Galetti et al 2013, Martinson andFagan 2014). Our results suggest that interactions among species within the same trophic level can play an important, yet overlooked, role in regulating the effects of fragmentation on biodiversity and ecosystem function.…”
Section: Discussioncontrasting
confidence: 66%
“…Despite clear experimental evidence of the impact of top predators on grassland insect herbivores (for a review see Schmitz 2010), empirical findings generally emphasize bottom-up control from plants (Haddad et al 2009;Borer et al 2012;Rzanny et al 2013). Our results confirm the well-documented sensitivity of top predators to landscape alteration (Purvis et al 2000;Martinson and Fagan 2014) but suggest that for grassland insect communities, the decline of top predators does not necessarily lead to predator-mediated effects on herbivore communities. However, recent studies have shown that the regulatory effect of top predators on insects can be context dependent as a function of seasonality (Gratton and Denno 2003), wind speed (Barton 2014), and especially temperature (Hoekman 2010;Shurin et al 2012;Barton and Ives 2014).…”
Section: Discussionsupporting
confidence: 46%
“…7; and strong: DAIC 1 10 (after Burnham and Anderson 2002 control of insect primary consumers, from mixed predator resource to unidirectional resource regulation. Past work had made the connection between habitat fragmentation and the potential disruption of trophic control (Nelson et al 2013;Martinson and Fagan 2014). However, mechanistic linkages with multiple stressors have been needed to accurately describe potential effects of global change, which are typically multivariate in nature (i.e., simultaneous alterations to resource, consumers, and spatial dynamics).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because with increasing trophic level, the resource pool becomes sparse and locally unstable [1][2][3]. Parasitoids live at the third and fourth trophic levels and are an important part of virtually all insect communities [4].…”
Section: Introductionmentioning
confidence: 99%